The Avifauna value of Lake Erçek (Van, Turkey) - Biler, Levent; Çelik, Emrah (Şırnak Üniversitesi, 2021)
Studies on the valuation of biodiversity are mainly prepared with market value, non-market value, and ecosystem value. Thus, the contingent valuation method (CVM) is mostly used. The direct valuation of biodiversity almost does not exist. In this study, bird counts of Lake Erçek have complied, and the highest counted number for the species was used. The valuation of the avifauna was made using the compensation fees within the scope of the Turkish Central Hunting Commission Decisions 2020-2021. In Lake Erçek a total of 183 bird species were recorded, and the avifauna value was calculated as 203.084.660,00 TL.
Keywords: Biodiversity value; The Central Hunting Commission; Compensation fees